A Comparative Study On Application Of Regulation Of Hygiene Education Dated 5 July 2013 Between Göynük And Güdül Counties - Mehmet Ruhi Gökmoğol (Journal of Social and Administrative Sciences, 2014)
Regulation of Hygiene Education has been published in compliance with the EU acquis on July 5, 2013 and has become valid on July 5, 2014. This study was conducted to determine the effect of local governments on increasing awareness and to increase the level of awareness as a result of the application of the trainings in Goynuk and Gudul in accordance with the regulations. During this study; questions have been asked by survey techniques and the responses have been analyzed by Student's t-test. In the study, it was observed that awareness of employees and employers was increased when the training was completed; whereas the level of awareness of the employees and employers not receiving training were quite low. It was understood that awareness is developed according to the importance given by the local authorities having audit liability.
Keywords: L60; L66; 330; Hygiene; Education; Food Safety; Food